THE INFLUENCE OF COMPETENCE AND MOTIVATION ON MIDWIFE PERFORMENCE IN NORMAL CHILDBIRD IN PUSKESMAS CIMANGGIS 2015 - maya latifatul masrurroh (Journal of Applied Health Management and Technology, 2020)
Based on data obtained from city Health Department depok In 2014 there were 17 cases of maternal deaths that are scattered throughout the District in Depok. PHC which has the highest number of midwives health workers are expected to contribute aid delivery by health personnel is high, but in District Cimanggis deliveries with health professionals (90.1%) is still below Depok (91.0%). The purpose of this study was to determine the effect midwife competencies and motivation to work on the performance of midwife of normal delivery care (APN) in the sub-district Puskesmas Cimanggis Year 2015. Desain study used cross sectional using a qualitative approach. The population in this study throughout the midwife who works at sub-district Puskesmas Cimanggis. In this study, using a total sampling of 30 midwives. The analytical method used is Structural Equation Model (SEM) using SmartPLS 2.0 and SPSS 18. The results showed variable performance of midwife in the application of normal delivery care (APN) in the sub-district Puskesmas Cimanggis directly influenced by the competence of midwives (51.4%) and motivation to work (34.0%), while other factors not studied variables affect the performance of midwives at 14.6% is recommended to further improve the performance of midwives in applying the normal delivery care (APN) by providing training competence normal delivery care (APN) and provide reward for midwives who have good performance so as to motivate the other midwives to improve the performance.